ORIGARUEN: MEDIA PEMBELAJARAN BERBASIS ORIGAMI “YOSHIMOTO CUBE” UNTUK MENDUKUNG KECERDASAN SPASIAL SISWA - Putri Rahmawati; Muhamad Toyib (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Spatial intelligence is difficult to develop in conventional learning. Even the implementation of these capabilities is still not considered. An alternative to the problems obtained is by creating learning innovations related to spatial intelligence. This development research aims to develop an origami-based learning media, namely Origaruen, which is valid and practical to support students' spatial intelligence. The model applied in the research and development procedure in this research is the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this study were 30 grade IX students of Muhammadiyah Junior High School, Kottabarat Special Program, Surakarta. The data was taken using a validity test questionnaire aimed at media experts, material experts, learning practitioners and students as well as spatial intelligence tests given to students. The data is taken using questionnaires and tests. The results showed that the development of Origaruen learning media is valid and practical to use and able to support students' spatial intelligence. Origaruen media can be an innovation in mathematics learning that can be used in an effort to support students' spatial intelligence.